Juridical Review of the Authority of the Constitutional Court in Settlement of General Election Disputes - Rasji Rasji; Nathalie Cristine Lumban Gaol; Zahra Alsabilah (CV. Rayyan Dwi Bharata, 2023)
Indonesia as a democratic country cannot be separated from the voice of the people in running its government. Every Indonesian citizen has the right to vote and be elected as stipulated in Law Number 39 of 1999 concerning Human Rights. As a milestone in the embodiment of the principles of democracy, general elections to elect representatives of the people must be based on the voice of the people. In the general election process, it is not uncommon for errors to occur in determining the results of the vote acquisition results which can lead to a particular conflict. Taking into account the error in determining the results of the vote acquisition or what is commonly referred to as the General Election Result Dispute (PHPU), it is necessary to have a method of settlement that can be carried out by the Constitutional Court. In this case the author examines what is the authority of the Constitutional Court in resolving disputes over the Obtaining of General Election Results (PHPU) and regarding the procedures for resolving disputes over the Obtaining of General Election Results (PHPU) in accordance with existing laws and regulations.